Formal Grounded Theory: Knowing When to Come Out of the Rain - Vivian B. Martin (Grounded Theory Review: An International Journal, 2017)
Getting started on a formal grounded theory is daunting for many grounded theorists, but now, as I tweak a nearly complete one, I find that knowing when to stop, to come in out of the rain, so to speak, can be a challenge, too.